Evaluating Volunteer Motivation for Sea Turtle Conservation in Florida - Bianca M. Bradford; Glenn D. Israel (EDIS)
Understanding volunteer motivation has been widely recognized by both researchers and managers as a valuable component of volunteer management (Cnaan & Goldberg-Glen, 1991; Harrison, 1995). Some studies have shown that highly motivated volunteers serve longer than volunteers who do not have their needs met through service (Omoto & Snyder, 1995). No study, however, has fully explored the roles that volunteers play in sea turtle conservation. To fill this gap, we conducted a study to reveal the motivations and experiences of people who volunteer for sea turtle conservation in Florida. We focused on three questions: What kind of people are sea turtle volunteers? Why do they volunteer? And, what do volunteers do? We collected data from volunteers and their supervisors to answer these questions. This document is AEC 372, a publication of the Agricultural Education and Communication Department, Florida Cooperative Extension Service, Institute of Agricultural and Food Sciences, University of Florida. Publication date May, 2004.